2020
DOI: 10.48550/arxiv.2007.07413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 16 deg$^2$ survey of emission-line galaxies at z<1.6 from HSC-SSP PDR2 and CHORUS

Masao Hayashi,
Rhythm Shimakawa,
Masayuki Tanaka
et al.

Abstract: We have conducted a comprehensive survey of emission-line galaxies at z < ∼ 1.6 based on narrowband (NB) imaging data taken with Hyper Suprime-Cam (HSC) on the Subaru telescope. In this paper, we update the catalogs of Hα, [OIII], and [OII] emission-line galaxies using the data from the second Public Data Release (PDR2) of Subaru Strategic Program (SSP) of HSC and Cosmic HydrOgen Reionization Unveiled with Subaru (CHORUS) survey along with the spectroscopic redshifts for 2,019 emission-line galaxies selected w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…We have derived the SFRD by integrating the LF, employing the Kennicutt (1998) relationship andKroupa (2001) IMF. We have found that the data from Khostovan et al (2015) and from Hayashi et al (2020) are at least ∼ 0.25 dex higher. This difference seems to come for our low value of φ * when compared with other results from literature (Ly et al 2007, Drake et al 2013or Hayashi et al 2013 and may be caused by the uncertainties presented in the normalisation of the LF due to CV effects.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…We have derived the SFRD by integrating the LF, employing the Kennicutt (1998) relationship andKroupa (2001) IMF. We have found that the data from Khostovan et al (2015) and from Hayashi et al (2020) are at least ∼ 0.25 dex higher. This difference seems to come for our low value of φ * when compared with other results from literature (Ly et al 2007, Drake et al 2013or Hayashi et al 2013 and may be caused by the uncertainties presented in the normalisation of the LF due to CV effects.…”
Section: Discussionmentioning
confidence: 70%
“…We note that these points are not extinction-corrected, so they are a lower limit for the SFRD, as indicated by the cyan arrows.The filled black circles are data from Khostovan et al (2015). The filled diamonds are data from Hayashi et al (2020). The result of this work is represented by the open square.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations